PENETAPAN TUJUAN DAN INDIKATOR KINERJA SEKOLAH DALAM PENINGKATAN MUTU PEMBELAJARAN DI SMP NEGERI 3 CINTAPURI DARUSSALAM - Muhammad Rindi; Zurjani Ilmi; Suhaimi; Sulistiyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The determination of performance goals and indicators in schools plays an important role in improving the quality of education management and learning outcomes. This study aims to analyze the process of determining performance goals and indicators implemented at SMP Negeri 3 Cintapuri Darussalam, Cintapuri Darussalam District. This research used a qualitative approach with interview techniques as the main data collection method. The informants consisted of the principal and a fifth- teacher. The results show that the determination of school performance goals begins with the evaluation of the previous year's program and is aligned with the school’s vision and mission. The formulation of goals is carried out collaboratively through meetings involving teachers and education staff. The indicators used to measure performance include classroom orderliness, the implementation of positive discipline, constructive feedback to students, and improvement of student learning outcomes. The use of the Ruang GTK platform also supports the monitoring and evaluation of teacher performance. The study concludes that clear performance goals and indicators contribute to improving the effectiveness of school management and learning quality.